PERAN PENDIDIKAN ISLAM DALAM MEMBENTUK PERILAKU SOSIAL MAHASISWA STAI NIDA EL-ADABI BOGOR - Sutarto (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2023)
This study aims to examine the role of Islamic education in shaping the social behavior of students at STAI Nida El-Adabi Bogor. The concept of Islamic education, student social behavior, and the factors that influence both are examined through a literature review. The research method used was a case study with the participation of a number of students at STAI Nida El-Adabi Bogor with data collection techniques through interviews and observation of a sample of students.The results of the study show that Islamic education has a positive role in shaping the social behavior of students at STAI Nida El-Adabi Bogor, such as increasing empathy, tolerance and independence. Factors such as a conducive tertiary environment, effective religious teaching, and the important role of the family in imparting religious values also influence the role of Islamic education in shaping students' social behavior. This research is expected to provide a broader understanding and view of the importance of Islamic education in shaping student social behavior. The implication of this research is that quality Islamic education can improve students' social behavior, so it needs to be considered in the development of an Islamic education curriculum in tertiary institutions. Suggestions for further research are to conduct broader research with a larger number of participants and involve universities in a wider area.